Acetaminophen at Different Doses Protects Brain Microsomal Ca2+-ATPase and the Antioxidant Redox System in Rats - Naziroglu, Mustafa; Cihangir Uguz, A.; Kocak, Ahmet; Bal, Ramazan (Springer, 2009)
Acetaminophen, an analgesic and antipyretic drug, rescues neuronal cells from mitochondrial redox impairment and reactive oxygen species (ROS). Excessive administration of acetaminophen above the recommended daily dose range has some negative effects on the brain. We investigated the effects of different doses of acetaminophen on Ca2+-ATPase and the antioxidant redox system in rats. Seventy rats were randomly divided into seven equal groups. The first was used for the control. One dose of 5, 10, 20, 100, 200, and 500 mg/kg acetaminophen was intraperitoneally administered to rats constituting the second, third, fourth, fifth, sixth, and seventh groups, respectively. After 24 h, brain cortical samples were taken and brain microsomal samples were obtained by ultracentrifugation. Brain and microsomal lipid peroxidation (LP) and brain calcium levels in the sixth and seventh groups were increased compared to control. LP levels in the second, third, and forth groups; brain vitamin E levels; brain and microsomal glutathione peroxidase (GSH-Px); and Ca2+-ATPase activity in the sixth and seventh groups were lower than in control, although brain vitamin E concentrations in the second, third, fourth, and fifth groups and microsomal GSH-Px activity in the third and fourth groups were higher than in control. Brain cortical beta-carotene and vitamin A concentrations did not differ in the seven groups. In conclusion, 5-100 mg/kg acetaminophen seems to have protective effects on oxidative stress-induced brain toxicity by inhibiting free radicals and supporting the antioxidant redox system.
Keywords: Acetaminophen; Antioxidant; Oxidative stress; Brain; Apoptosis; Ca2+-ATPase; Rat